Analisis Korelasi Sikap Ilmiah dan Hasil Belajar Biologi : (Analysis Correlation of Scientific Attitude and Biological Learning Outcomes) - Muhammad Nasrul Mustain; Bonita Hirza; Rusdy A Siroj (BIODIK, 2021)
This study intends to provide information: (1) the level of scientific attitude ability of Biology students (2) the level of learning outcomes of Biology lessons (3) see the relationship between scientific attitudes and learning outcomes in Biology. The type of research was correlation research. The research population was all high school students in Ogan Komering ilir district, which is taken 30% of the sample area so that 5 districts represent the population. The sample technique used is perposive sampling with a total of 1827 students and the instruments used are scientific attitude questionnaires and odd semester test scores for the 2020/2021 school year. The results showed ((1) students' scientific attitude obtained an average score of 89 in the medium category, (2) cognitive learning outcomes of Biology students obtained an average score of 82 in the medium category, (3) There was a significant relationship between scientific attitudes and cognitive learning outcomes in Biology lessons with a relationship level of 0.655 including a "strong" correlation. Abstrak. Penelitian ini bermaksud untuk memberikan informasi: (1) tingkat kemampuan sikap ilmiah siswa pelajaran Biologi (2) tingkat kemampuan hasil belajar pelajaran Biologi (3) melihat hubungan antara sikap ilmiah dan hasil belajar pelajaran Biologi. Jenis penelitian ini adalah penelitian korelasi. Populasi penelitian adalah seluruh siswa Sekolah Menengah Atas di kabupaten Ogan Komering ilir, yang diambil 30% dari sampel wilayah sehingga 5 kabupaten mewakili populasi. Tekhnik sampel yang digunakan adalah perposive sampling dengan total siswa adalah 1827 siswa dan instrumen yang digunakan adalah kuisioner sikap ilmiah dan nilai ulangan semester ganjil tahun ajaran 2020/2021. Hasil penelitian didapatkan bahwa; (1) sikap ilmiah siswa memperoleh skor rata-rata sebesar 89 dengan kategori sedang, (2) Hasil belajar Kognitif siswa pelajaran Biologi memperoleh skor rata-rata sebesar 82 dengan kategori sedang, (3) Terdapat hubungan signifikan antara sikap ilmiah dengan hasil belajar Kognitif pelajaran Biologi dengan tingkatan hubungan sebesar 0,655 termasuk dalam korelasi â€œkuatâ€.Â